Ultrasound-guided fine-needle aspiration cytology as a diagnostic tool in comparison to ultrasound and MRI for staging in oral- and oropharyngeal squamous cell tumors. Issue 2 (February 2016) - Souren, Cyriel; Kloss-Brandstätter, Anita; Stadler, Annika; Kross, Kenneth; Yamauchi, Kensuke; Ketelsen, Dominik; Kessler, Peter; Lethaus, Bernd
Abstract: The aim of this retrospective study was to test the diagnostic performance of ultrasound guided fine-needle aspiration cytology (USFNAC) in comparison to ultrasound (US) and magnetic resonance imaging (MRI) for detecting lymph node metastases in patients with squamous cell carcinoma of the oral and oropharyngeal region. 143 patients with oral cavity and oropharyngeal squamous cell carcinoma were included in the study. US, USFNAC and MRI were routinely performed prior to neck dissection. The results of the imaging studies were compared to histopathology. The sensitivity of MRI was highest at 83%, followed by USFNAC and US at 81% and 73%, respectively. The specificity was highest for FNAC at 100%, followed by MRI and US at 76% and 45%, respectively. Positive predictive value was highest for USFNAC 100%, US 57%, MRI 75% and negative predictive value was 77%, 69% and 84%, respectively. In our patient group with oral and oropharyngeal carcinoma, MRI had a higher sensitivity than USFNAC and US alone. USFNAC provided additional staging information. Especially in an uncertain lymph node situation it can facilitate and optimize preoperative planning with a specificity of 100% regarding tissue entity of cervical lymph nodes.